Coping with Stress Questionnaire: Application of the four-factor model - Grakauskas, Žygimantas; Valickas, Gintautas (Psichologija, 2006)
The article introduces the Lithuanian stress coping assessment method. The lack of stress coping assessment methods adapted for the Lithuanian population fostered its composition. The method was constructed using the strategy of empirical scale development. The research was carried out in three stages. In the first and second stages, statements were selected from various stress coping questionnaires (WCQ, COPE, CISS etc.) and classified using the mathematical model of explanatory factor analysis. In the first stage, the original list consisting of 167 statements was submitted to 178 participants of the study. In the second stage, the list consisting of 90 statements was submitted to 147 participants. The participants were students of Vilnius University and the General Jonas Žemaitis Military Academy of Lithuania, average age – 20.4 years. On the basis of mathematical criteria and semantic analysis of the statements, the number of the statements was reduced to 24 in the final version of the questionnaire; 4 factors were xtracted: social support, problem solving, emotional discharge, avoidance. 208 participants took part in the third stage of the study, during which some psychometrical characteristics of the questionnaire were assessed. It was established that these four factors explain for 47.93 per cent of data dispersion. The following indexes of scales reliability (Cronbach’s alpha) were found: social support (α = 0.832), problem solving (α = 0.760), emotional discharge (α = 0.721), avoidance (α = 0.624). Confirmatory factor analysis data indicate a satisfactory suitability of the model of four factors (Chi-Square = 140.81; RMSEA = 0.055; GFI = 0.89; CFI = 0.87; NNFI = 0.84).While composing the questionnaire, the problem of optimal balance was encountered between choosing a good method in the sense of content and a method distinctive characterized by good psychometrical characteristics. There is a plan in the future to verify the psychometrical characteristic of the composed stress coping assessment method on the basis of data of a more representative sample, to assess the relation of the questionnaire to the other methods of stress coping and to improve separate scales of the questionnaire, especially those dealing with the factor of avoidance.
Keywords: coping with stress; stress coping strategies; stress coping measurement